Expressed Emotions and Depressive Symptoms in Caregivers of Adolescents with First‐Onset Anorexia Nervosa—A Long‐Term Investigation over 2.5 Years. (January 2017) - Schwarte, Reinhild; Timmesfeld, Nina; Dempfle, Astrid; Krei, Melanie; Egberts, Karin; Jaite, Charlotte; Fleischhaker, Christian; Wewetzer, Christoph; Herpertz‐Dahlmann, Beate; Seitz, Jochen; Bühren, Katharina
Abstract: Objective: High levels of expressed emotions (EE) and depressive symptoms (DS) are often found in caregivers of patients with anorexia nervosa (AN). Both parameters are considered to influence AN symptoms of the patient. Methods: One hundred seventy adolescent women with AN and their caregivers were assessed at admission, discharge, at 1‐year and 2.5‐year follow up to evaluate AN symptoms of the patient and EE and DS of caregivers. Results: The EE and DS were elevated at admission and decreased during treatment, criticism (as part of EE) exhibited again at the 2.5‐year follow up. Caregivers of more severely ill patients reported significantly greater levels of EE and DS. Mothers were more affected than fathers. EE and DS were interrelated. Conclusion: Caregivers of adolescent AN patients suffer from elevated levels of EE and DS. Further studies are needed to examine whether therapeutic interventions to reduce caregivers' EE and DS might have a positive influence on treatment outcome. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.